Tanggung Jawab Notaris Setelah Berakhir Masa Jabatan Terhadap Protokol Notaris (Studi Kasus Putusan Pengadilan Negeri Pontianak Nomor 119/Pdt.G/2013/Pn.Ptk) - An’Umillah, Asfari Syukran (UNES Law Review, 2023)
The Notary Protocol must be kept by the Notary for an unlimited period of time. Article 63 Paragraph (5) of the Notary Office Law states that the Notary's protocol from another Notary whose submission is 25 years old or more, is submitted to the Notary Regional Supervisory Council, but when there is a problem in the Notary's deed that the protocols provider is, the Notary's protocols provider is involved. perima protocols, problems with the problems above, what are the considerations of the judge in the decision on case number 119/Pdt.G/2013/PN Ptk related to the Notary's Responsibilities after the end of the term of office for the Notary's protocol? 119/Pdt.G/2013/PN Ptk?, Research Objectives To find out the judge's considerations in the case decision number 119/Pdt.G/2013/PN Ptk associated with Notary Responsibilities after the end of the term of office for Notary protocols and To find out responsibilities The notary who has retired according to the protocol is involved in case number 119/Pdt.G/2013/PN Ptk. This study uses a normative juridical research approach. The main material for this research is secondary data obtained from various pre-existing data based on laws, literature and other legal studies. Primary data from primary, secondary and tertiary legal materials, using qualitative data analysis and presented in a descriptive form. The results of this study indicate that: The legal considerations of the judges at the Pontianak District Court in deciding to declare Defendants I, II, IV and V had violated the law (Onrechtmatige daad) and the applicable laws and regulations and were very contrary to the sense of justice and legal certainty. Breaking the law (Onrechtmatige daad) Unlawful acts committed by the defendant, namely selling land, namely HGB, declared illegal and null and void. Regarding the Responsibilities of Notaries who have Retired Against Their Protocols Associated in Case Number 119/Pdt.G/2013/Pn Ptk, whereas the Notary Giving the protocol (Defendant III) Notary in this case does not violate the applicable legal provisions, because the Notary has made a power of attorney in accordance with the request of the power of attorney to the power of attorney.